HAMBATAN PARTISIPASI PETANI DALAM PENGEMBANGAN PADI ORGANIK DI KABUPATEN TASIKMALAYA - Mimin Aminah (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
Farmers' participation in the group is required to overcome the various obstacles of deficiency, commitment development, motivation encouragement, credibility establishment, and bargaining power strengthening. Results of processing using ISM indicated that the end target of the completion of participation obstacles is to resolve the bottleneck of "Keeping drains impurities from chemical", "Mutual in doing work in the rice fields," as well as "Formulating  fertilizers, organic pesticides, and MOL". To overcome the above-mentioned barriers to participation, resolution of obstacle to participation "Group meeting" must be conquered in advance. Therefore, in order to increase the participation of farmers, there is a need make more detailed study on the issue of the deficiency, commitment, motivation, credibility, and the bargaining power of farmers owned, to find out opportunities to improve those factors. Participation in "Group meeting" should be a continuous effort